Análisis artístico y estético de tres obras de Henry Moore, como referente para una propuesta escultórica - Abad Abad, Cristian Ramiro (2015)
The sculpture as a way of artistic expression has been present during the humanity's development and evolution, to communicatethe cognitive aspects that diversified its ways to see, feel and capture the nature and the life. For this reason the present investigation is guided to establish the existent correlations between the conceptions of the human existence and its repercussion in the design and execution of sculptural works, to achieve this objective was necessary using bibliographical references that allow observe and demonstrate how the different milestones of the history and its philosophical currents consequents influenced in the production of the artists, for example Henry Moore whose works always maintained logic with the cultural and historical moment of this temporal and spatial context.